Juvenile Huntington and intrafamily phenocopy, about two cases - Silva-Bullón, Midiam (2023)
Huntington’s disease (HD) is an inherited neurodegenerative disorder with an always fatal outcome. Other disorders resemble the symptoms of this disease and are called phenocopies. The cases of two brothers in a family affected with a phenotype compatible with HD, are presented, one of them an intrafamilial phenocopy, characterized by choreic syndrome, abnormal behavior, and negative HD genetic testing. The index case evolves with a juvenile-onset slowly progressive parkinsonian form of HD that, in addition, presents neuropsychiatric symptoms with minimal response to symptomatic treatment with dopamine antagonists. The older brother, the intrafamilial phenocopy, experienced severe facial cervicofacial and cervical dyskinetic movements, psychosis, and preserved cognition. In conclusion, the HD phenocopies might occur even within a known, genetically confirmed HD family. It is recommended to perform a detailed neurological examination together with appropriate genetic testing in all cases with clinical suspicious of HD, including direct family members of HD affected individuals.